Informed consent and clinical trial participation: Perspectives from a Ghanaian community - Akrong, L.; Horstman, K.; Arhinful, D.K. (Making Global Health Care Innovation Work: Standardization and Localization, 2014)
Clinical research continues to expand globally. Lower-income countries have become popular destinations for research institutions and pharmaceutical companies in which to conduct clinical trials (Ballantyne 2010; Emanuel et al. 2004; Glickman et al. 2009). To illustrate, Ghana, a country relatively new to clinical research (Ogutu et al. 2010; Ghana-Michigan Collaborative 2010), reported having thirteen registered clinical trials in operation in 2012, according to the government¡¦s Food and Drug Board that regulates this work (Food and Drug 2012). Of these trials, twelve were sponsored by non-African institutions, with the remaining one funded by a Tanzanian research institution (Food and Drug 2012).1 The pharmaceutical industry is aware that running trials in the lower-income countries is more cost effective than in higher-income countries (Petryna 2007; Schuklenk 2010). In lower-income countries like Ghana, participants are often targeted as preferable, ¡§treatment-naïve¡¨ trial candidates, meaning individuals who have not been exposed to drugs that could potentially interfere with clinical trial results (Frimpong-Mansoh 2008; Mbuagbaw et al. 2011; Petryna 2007).
Keywords: Clinical Trial Participation; Ghana; Food and Drug Board